388 Percutaneous Transluminal Angioplasty and/or Stenting for the Treatment of Basilar Artery Stenosis: A Systematic Review and Meta-Analysis. (April 2023) - Palmisciano, Paolo; Hoz, Samer Saad; Algburi, Hagar A.; Ventre, Giancarlo Javier; Street, Seth; Agyeman, Nana; Robinson, Michael; Smith, Matthew; Shirani, Peyman; Grossman, Aaron W.; Prestigiacomo, Charles J.
Abstract : INTRODUCTION: Basilar artery stenosis (BAS) carries high morbidity and mortality, with variable outcomes reported after endovascular treatments. METHODS: PubMed, EMBASE, Web-of-Science, Scopus, and Cochrane were searched upon the PRISMA guidelines to include studies describing PTAS for BAS. Pooled rates of intervention-related complications and outcomes were analyzed with random-effect model meta-analyses. RESULTS: We included 25 studies comprising 1016 patients. Patients were mostly male (79.5%), with hypertension (81.1%) and/or dyslipidemia (56.4%), and presenting with transient ischemic attack (54.4%) or stroke (45.6%). BAS frequently involved the middle basilar artery (51.4%), and were mostly classified as Mori-B (57.4%). PTAS for BAS was indicated in patients with severe (≥50%-70%) symptomatic BAS refractory to dual antiplatelet therapy. Patients underwent angioplasty (95.5%) and/or stenting (92.2%), preferably using Wingspan or Apollo stents. Median baseline BAS was 81% (range, 53%-99%), while median post-intervention BAS was 13% (0%-75%). Actuarial rates of successful intervention and "good" final outcome were 100% (95% CI: 100%-100%) and 89% (95% CI: 85%-93%). Intervention-related recurrent ischemic stroke occurred in 85 patients (8.3%) with actuarial rates of 5% (95% CI: 4%-7%), and was differentiated into perforator (5.4%), in-stent (2.6%), and embolic (0.4%). Actuarial rates of intervention-related dissection, restenosis, and death were 0% (95% CI: 0%-0%), 1% (95%CI: 0%-1%), and 0% (95% CI: 0%-2%). CONCLUSIONS: Elective PTAS is safe and effective in selected patients with medically-refractory, severe, symptomatic, and non-acute BAS. Different stent types and angioplasty-assisted procedures should be considered based on specific clinico-radiological characteristics of the lesions.